Origin of acetylcholine antagonism in ELIC, a bacterial pentameric ligand-gated ion channel - Mykhaylo Slobodyanyuk; Jesús A. Banda-Vázquez; Mackenzie J. Thompson; Rebecca A. Dean; John E. Baenziger; Roberto A. Chica; Corrie J. B. daCosta (Communications Biology, 2022)
A structural and functional study of the prokaryotic ligand-gated ion channel, ELIC, provides insight into the origin of agonism and antagonism at nicotinic acetylcholine receptors.